PENERAPAN ALGORITMA CLUSTERING K-MEANS PADA PENGELOMPOKAN DAERAH TEMPAT SAMPAH DI LINGKUNGAN KAMPUS PONDOK LABU UPN VETERAN JAKARTA - Ali Hasyimi, (2021)
A clean environment is one of the needs of society in life. Efforts to create a clean environment continue to be carried out in tandem with various new methods applied in the environmental treatment system in the community. One of the methods and innovations applied in the community is the use of Data Mining and Machine Learning in processing solid waste in order to create a more effective and efficient solid waste treatment system. The flexible but efficient application of technology makes performance improvements and easier to obtain information from various activities and from various kinds of problem solving. This has led the author to take the initiative to conduct research related to the implementation of Data Mining and Machine Learning on environmental issues, especially on solid waste processing. This study applies the Data Mining method, namely Cluster Analysis with the KMeans algorithm to manage data on the distribution of trash bins in the UPN Veteran Jakarta environment which produces information from the dataset and visualizes the distribution of trash cans.